Cellular automaton model simulating spatiotemporal patterns, phase transitions and concave growth pattern of oscillations in traffic flow. (November 2016) - Tian, Junfang; Li, Guangyu; Treiber, Martin; Jiang, Rui; Jia, Ning; Ma, Shoufeng
Highlights: A Two-state Safe-speed Model is developed to simulate empirical and experimental findings. The concave growth pattern of traffic oscillations is well replicated. The empirical NGSIM detector data can be simulated with a quantitative agreement. The observed spatiotemporal patterns and phase transitions of traffic flow are reproduced. Abstract: This paper firstly shows that a recent model (Tian et al., Transpn. Res. B 71, 138–157, 2015) is not able to replicate well the concave growth pattern of traffic oscillations (i.e., the standard deviation of speed is a concave function of the vehicle number in the platoon) observed from car following experiments. We propose an improved model by introducing a safe speed and the logistic function for the randomization probability. Simulations show that the improved model can reproduce well the metastable state, the spatiotemporal patterns, and the phase transitions of traffic flow. Calibration and validation results show that the concave growth pattern of oscillations and the empirical detector data can be simulated with a quantitative agreement.